Can All the Sardinian Varieties Support the PDO "Sardegna" Virgin Olive Oil?. Issue 3 (21st October 2018) - Deiana, Pierfrancesco; Santona, Mario; Dettori, Sandro; Molinu, Maria G.; Dore, Antonio; Culeddu, Nicola; Azara, Emanuela; Naziri, Eleni; Tsimidou, Maria Z.
Abstract : Protected Designation of Origin (PDO) labels are important tools to promote high quality virgin olive oils (VOO). To better valorize and differentiate among others these labeled products it is necessary to have a deep knowledge of characteristics and features of the monovarietal VOOs that are used. In Sardinia, only one PDO, named "Sardegna, " is registered. Drupes from several local varieties are mixed up before pressing. Four are the principal autochthonous Sardinian varieties: Bosana, Tonda di Cagliari, Tonda di Villacidro, Semidana, and respective synonyms. This study examines the chemical and nutritional characteristics of monovarietal VOOs of some of the varieties that comprise the label with the aim to establish the identity and natural variability of the registered product. Results are compared with those from some minor Sardinian and Italian cultivars, all grown under the same agronomic and environmental conditions. Data for the fatty acid and sterol composition together with those for some specific nutrient and non nutrient antioxidants are used to investigate whether the mixing up of many different varieties is favorable in the production of this particular product. PDO varieties achieve broadly minimum quality levels requested by the label regulation and express some specific characteristics in accordance to genetic similarities. Practical Applications : Knowledge of chemical composition of VOOs from minor local varieties is of great interest for the promotion of products typical of a specific territory and to improve quality and competitiveness of protected denominations labels. The characterization of VOO admitted to a PDO can help producers to optimize blends obtaining specific nutritional and sensorial features. Moreover, findings are important to highlight some distinctive features among genetic groups that might be useful for further supporting the integrity of the registered product in the near future. PDO "Sardegna" is the only quality label for EVOO registered in Sardinia (Italy). It must be characterized at least for the 80% by the four principal autochthonous Sardinian varieties: Bosana, Semidana, Tonda di Cagliari, Tonda di Villacidro, and their other names. VOO composition of 14 of the Sardinian varieties that can be used in the production of the registered product, with the aim to establish its identity and natural variability of this label are analyzed. Abstract : PDO "Sardegna" is the only quality label for EVOO registered in Sardinia (Italy). It must be characterized at least for the 80% by the four principal autochthonous Sardinian varieties: Bosana, Semidana, Tonda di Cagliari, Tonda di Villacidro, and their other names. VOO composition of 14 of the Sardinian varieties that can be used in the production of the registered product, with the aim to establish its identity and natural variability of this label are analyzed.